Políticas públicas e estratégia sustentável de combate à fome: O caso do PAA-leite no município de Quixeramobim - Ceará - Oliveira, Lúcia Andrea Sindeaux de (2011)
The present evaluates the impact of PAA – Milk in the county of Quixeramobim-CE, on socioeconomic conditions of farmers benefited by the program. Concerning data were obtained from a field survery in January, 2011, in the city of Quixeramobim. As techniques analyses were used the tabular one, graphical and descriptive, the Student t and Kruskal-Wallis test6 to compare means and proportions respectively. In relation to the analysis of interviewees life standard, it was referred the calculation of Quality of Life Index (QLI) of beneficiaries and non-beneficiaries. The main results point out that the average age of beneficiaries is lower than that of non-beneficiaries and the education level of beneficiaries is greater than that of non-beneficiaries. The main occupation of interviewed people is agriculture. The small farm is m ore common in the in both groups and most have the ownership of this property. The manpower used most often by respondents is the familiar one. The distribution of annual income of b eneficiaries has a higher proportion if compared to non-beneficiaires in agricultural activities and a greater representation in livestock income. The QLI is high concerning on beneficiaries and medium for non-beneficiaries. The largest contributions came from the came from the QLI housing conditions, in terms of lasting goods, and the lower minimum from health conditions. PAA - Milk has been increasing beneficiaries, purchasing power contributing to provide a better quality of life.